(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research focuses on the correlation between the organizational climate and four important organizational activities namely communication, decision making and conflict solving. Organizational climate which can be described as the employees’ perceptions of the organization’s environment is assumed to affect the ways in which the employees interact, problem solve and decide. A quantitative survey and qualitative interviews were used to collect data from employees in different industries. The measures employed in the study included those that have been developed and validated to measure dimensions of organizational climate, communication satisfaction, decision making and conflict solving styles. The results suggest that support, autonomy and openness are positively related to communication satisfaction, decision making and conflict management. More specifically, supportive climates were characterised by higher levels of communication openness and a more cooperative approach to conflict than a competitive or avoidant one. The results of the regression analysis showed that the openness of communication and supportiveness were the most significant correlates of positive communication and conflict-solving behaviors. The qualitative data supported these conclusions, indicating that people in open and autonomous work environments reported they were able to participate in decision making and manage conflicts constructively.